Hypothetical Learning Trajectory (HLT) to Build Understanding of Mathematics Education Students about What is and How to Apply Problem Based Learning (PBL) to Learn Mathematics - Surya, Francisca Yenuacrista; Dewi, Friesca Pra Utami; Julie, Hongki (Universitas Muhammadiyah Surakarta, 2021)
This study aims to (1) find out how Hypothetical Learning Trajectory (HLT) in problem base learning on teh topic of volume and surface area of a cube; (2) find out how the understanding of S1 students who take class D Micro Teaching courses regrading teh Problem Based Learning model. This type of research is design research. The subjects in this study were 15 students who took the Micro Teaching course in class D. The data analysis used in this study was data analysis by Miles and Huberman, namely reducing data, presenting data, drawing conclusions and verifying. In general, the research steps carried out are (1) the researcher conveys the learning objectives, namely helping students understand problem based learning; (2) the resercher gives apperception to the topic that is used as a problem-solving medium; (3) the researcher conveys the problem to be solved by the students; (4) students solve the problems given and are guided by researcher, then students present them; (5) evaluate the results of problem solving, then students draw conclusions from the activities they do during learning. Based on the results of interviews after going through the learning process, it can be concluded tha eleven students can only explain that PBL must begin by solving problem that aim to find a Mathematical concept, and four students can explain how the stages of learning that must be passed by students starting from giving problems to by discovering a Mathematical concept.